Sedimentary development and isotope analysis of deposits at the Cretaceous/Palaeogene transition in the Paraíba Basin, NE Brazil - Neumann, Virgínio Henrique; Barbosa, José Antônio; Silva, Maria Valberlândia Nascimento; Filho, Mário de Lima (Bogucki Wydawnictwo Naukowe, 2009)
New data are presented for three formations (Itamaracá, Gramame and Maria Farinha) and two boundaries (Campanian/Maastrichtian and Maastrichtian/Danian) in the Olinda Sub-basin of the Paraíba Basin. Currently accepted facies models, sequence stratigraphy characterizations, and stable-isotope data of carbon and oxygen are reviewed. The carbonate cement of the Itamaracá Formation sandstones shows carbon- and oxygen-isotope ratios consistent with a shallow-marine depositional environment: δ18O ranges from -0.8 to -2.7‰ PDB, and δ13C ranges from +1 to +2‰ PDB. Within the Itamaracá Formation, a maximum flooding surface at the Campanian/Maastrichtian transition has been identified. During the Maastrichtian, a Highstand System Tract was deposited, which shows an increase in temperature and marine bioproductivity as recorded by stable-isotope values (δ18O from -3 to -5‰ PDB, and δ13C values of -1.2, -0.3, 0.1 and +2.3‰ PDB). Just below the K/Pg boundary, the O-isotope signal indicates three warming phases, alternating with four cooling phases.
Keywords: NE Brazil; Cretaceous/Palaeogene boundary; carbon isotopes; oxygen isotopes